PROPOSED SCHEDULED WITNESSES TO SPEAK IN OPPOSITION TO PUBLIC HEALTH COUNCIL'S SMOKING RESTRICTION REGULATIONS ALBANY, NEW YORK 860114 (Tufts Archival Research Center, 2007)
Marginalia; List of proposed scheduled witnesses to speak in opposition to New York Public Health Council's smoking restriction regulations on January 14, 1986.